2001
DOI: 10.1159/000047612
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of a Cerebral Arteriovenous Malformation after Surgical Excision

Abstract: Complete resection of a cerebral arteriovenous malformation (AVM) should eliminate the future risk of an associated intracranial bleeding. Because total removal of an AVM may be difficult to assess at the time of surgery, postoperative angiography has become the accepted standard for documenting that complete removal has been achieved. However, even angiographically confirmed excision of an AVM does not completely exclude the possibility of rebleeding. Regrowth of an AVM with subsequent haemorrhage has been do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Cerebral AVMs are considered to be congenital lesions [4] and are characterized by a failure of the embryonic vascular plexus to fully differentiate and develop a mature capillary bed in the affected area. However, the de novo development and growth of AVMs [5,6,7,8,9,10] or regrowth following complete resection [11,12,13,14,15], which cannot be attributed only to the congenital pattern, have also been shown. Previous studies demonstrated an involvement of angiogenic factors in the pathogenesis of AVMs.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral AVMs are considered to be congenital lesions [4] and are characterized by a failure of the embryonic vascular plexus to fully differentiate and develop a mature capillary bed in the affected area. However, the de novo development and growth of AVMs [5,6,7,8,9,10] or regrowth following complete resection [11,12,13,14,15], which cannot be attributed only to the congenital pattern, have also been shown. Previous studies demonstrated an involvement of angiogenic factors in the pathogenesis of AVMs.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that recurrence caused by microshunts might remain invisible on early postoperative angiography. Some authors suggested that regrowth of childhood AVM may be attributable to the inherent nature of the development of an original abnormal vasculature 4) . Recurrence is definitely more common in children than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrent nidal core had to gather vessels from remote areas. From the review of literatures, we found 4 cases of recurrent AVMs that recruited the feeders from remote area for forming new nidus; three of four 10) had new deep arterial feeding vessels (choroidal arteries, lenticulostriate arteries) that were not present originally and the one of four 4) had deep arterial feeders (anterior and posterior choroidal arteries) initially and superficial arteries (branches of PCA and callosomarginarl artery) were then involved. Therefore, recurrence or regrowth should be an active process, and VEGF or innate angiogenetic potential may play a role in these processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations